In-stream wetland deposits, megadroughts, and cultural change in the northern Atacama Desert, Chile. Issue 1 (14th February 2019) - Tully, Craig D.; Rech, Jason A.; Workman, T. Race; Santoro, Calogero M.; Capriles, José M.; Gayo, Eugenia M.; Latorre, Claudio
Abstract: A key concern regarding current and future climate change is the possibility of sustained droughts that can have profound impacts on societies. As such, multiple paleoclimatic proxies are needed to identify megadroughts, the synoptic climatology responsible for these droughts, and their impacts on past and future societies. In the hyperarid Atacama Desert of northern Chile, many streams are characterized by perennial flow and support dense in-stream wetlands. These streams possess sequences of wetland deposits as fluvial terraces that record past changes in the water table. We mapped and radiocarbon dated a well-preserved sequence of in-stream wetland deposits along a 4.3-km reach of the Río San Salvador in the Calama basin to determine the relationship between regional climate change and the incision of in-stream wetlands. The Río San Salvador supported dense wetlands from 11.1 to 9.8, 6.4 to 3.5, 2.8 to 1.3, and 1.0 to 0.5 ka and incised at the end of each of these intervals. Comparison with other in-stream wetland sequences in the Atacama Desert, and with regional paleoclimatic archives, indicates that in-stream wetlands responded similarly to climatic changes by incising during periods of extended drought at 9.8, 3.5, 1.3, and 0.5 ka.